Clinical Case of a 23-Year-Old Patient with Moyamoya Disease and Epilepsy in Bulgaria - Ekaterina Viteva; Petar Vasilev; Georgi Vasilev; Kostadin Chompalov (MDPI AG, 2024)
Moyamoya disease is a cerebrovascular pathology characterized by progressive stenosis of the internal carotid arteries and their branches, leading to ischemic and/or hemorrhagic disorders of the cerebral circulation, primarily affecting children and young adults. We present a case of a 23-year-old woman with a history of recurrent cerebrovascular accidents since childhood. Despite experiencing focal motor seizures and transient ischemic attacks, her condition remained undiagnosed until 2006, when, at the age of 7, a digital subtraction angiography revealed characteristic bilateral internal carotid artery occlusions. Subsequent diagnostic challenges and treatments preceded a worsening of symptoms in adulthood, including generalized tonic-clonic seizures. Upon presentation to our clinic, the patient exhibited upper motor neuron syndrome and occipital lobe syndrome, consistent with the disease's pathophysiology, neuroimaging, and clinical manifestations. Imaging studies confirmed multiple ischemic lesions throughout the cerebral vasculature. Treatment adjustments were made due to the increased incidence of seizures, and the dose of her anti-seizure medication-divalproex sodium-was increased. This case underscores the diagnostic complexities and challenges in managing moyamoya disease, emphasizing the importance of early recognition and prompt intervention.